2004
DOI: 10.1097/01.asn.0000137879.97445.6e
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a Failed Kidney Transplant in Patients Who Are on Hemodialysis Is Associated with Chronic Inflammatory State and Erythropoietin Resistance

Abstract: Abstract. Patients returning to hemodialysis (HD) after failure of their kidney transplant suffer from high morbidity and mortality rates. It is common practice to keep failed kidney transplants in place. It is not known if these failed kidney transplants induce an inflammatory state that contributes to morbidity and mortality. In a single facility, patients starting on HD with failed kidney transplant were identified (Group A) and screened for the presence of chronic inflammatory state. Those with clinical sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
159
1
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(174 citation statements)
references
References 28 publications
5
159
1
9
Order By: Relevance
“…It has also been shown that in patients who return to hemodialysis after graft failure and who undergo nephrectomy have a lower high-sensitivity C-reactive protein level and lower requirements for rh-EPO with higher hemoglobin levels than in patients who have returned to hemodialysis but did not undergo nephrectomy (30). This "EPO resistance" mirrors that seen in other hemodialysis patients with elevated C-reactive protein levels (31).…”
Section: Causes and Correlatessupporting
confidence: 60%
“…It has also been shown that in patients who return to hemodialysis after graft failure and who undergo nephrectomy have a lower high-sensitivity C-reactive protein level and lower requirements for rh-EPO with higher hemoglobin levels than in patients who have returned to hemodialysis but did not undergo nephrectomy (30). This "EPO resistance" mirrors that seen in other hemodialysis patients with elevated C-reactive protein levels (31).…”
Section: Causes and Correlatessupporting
confidence: 60%
“…Renal allograft yetmezlikli hastalarda kronik inflamatuvar durum, artmış kardiyovasküler risk, süregelen immünsupres-yonun yol açtığı sorunlar (enfeksiyon, kanser) ve diyalize geç dönülmesi artmış mortalite oranı ile ilişkili olabilir (11,22,23).…”
Section: Renal Allograft Yetmezlikli Hastalarda Diyalize Dönüş Zamanıunclassified
“…Sonuçta allograft yetmezliği olup graft nefrektomi yapılmamış ve kronik inflamasyon bulguları gösteren rejeksiyon gelişmiş olan böbrek nakilli hastalarda transplant nefrektomi önerilmiştir (22). Öte yandan, renal allograft yetmezliği nedeniyle hemodiyalize dönen hastalarda halsizlik, iştahsızlık, ateş ve kilo kaybı gibi semptomlar olduğunda tüberküloz gibi infeksiyöz hastalıklar ve lenfoma gibi malign hastalıklar da ayırıcı tanıda düşünülmelidir.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Neunclassified
See 1 more Smart Citation
“…The observation that these patients suffer from disproportionately high rates of sepsis and infection-related mortality has led to the hypothesis that a history of prolonged and ongoing exposure to chronic immunosuppression may be mediating these risks (4,8,9). Moreover, the transplanted kidney itself may be an ongoing source of systemic inflammation and hypoalbuminemia even in the absence of overt clinical evidence of rejection (10). Taken together, the role of transplant-specific modifiable practices after graft loss, including the method and rapidity of immunosuppression tapering and/or the indications for and timing of transplant nephrectomy in improving outcomes after transplant failure, remain unclear (11)(12)(13)(14).…”
mentioning
confidence: 99%